2014
DOI: 10.1038/srep05612
|View full text |Cite
|
Sign up to set email alerts
|

High water level impedes the adaptation of Polygonum hydropiper to deep burial: Responses of biomass allocation and root morphology

Abstract: Many studies have investigated the individual effects of sedimentation or inundation on the performance of wetland plants, but few have examined the combined influence of these processes. Wetland plants might show greater morphological plasticity in response to inundation than to sedimentation when these processes occur simultaneously since inundation can negate the negative effects of burial on plant growth. Here, we evaluate this hypothesis by assessing growth of the emergent macrophyte Polygonum hydropiper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…A high rate of sedimentation inhibits the growth and colonization of all but highly specialized species13, which might be attributed to the low availability of oxygen and light in buried soils41113. In this study, only a few sedimentation-tolerant species were able to successfully colonize (e.g.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A high rate of sedimentation inhibits the growth and colonization of all but highly specialized species13, which might be attributed to the low availability of oxygen and light in buried soils41113. In this study, only a few sedimentation-tolerant species were able to successfully colonize (e.g.…”
Section: Discussionmentioning
confidence: 62%
“…As a result, only a few sedimentation-tolerant species can successfully colonize under heavy sedimentation. However, slight sedimentation may not inhibit or even stimulate the growth of some sand dune species because the deposited sediments can reduce water evaporation and temperature fluctuations1113. Therefore, vegetation characteristics will differ depending on the sedimentation rate in sand dunes.…”
mentioning
confidence: 99%
“…Moreover, the model was calibrated based on previous field observations and empirical assumptions, ignoring the plasticity of coastal vegetation. Pan et al 35. demonstrated that wetland plants can display morphological plasticity in response to inundation.…”
Section: Discussionmentioning
confidence: 99%
“…Dongting Lake (28°30'-30°20' N, 111°40'-113°10' E), the second largest freshwater lake in China with an area of 2620 km 2 , is located in the northern Hunan Province in a basin south of the Yangtze River, to which it is connected by three distributary channels (Pan et al, 2014; Fig. 1).…”
Section: Study Areamentioning
confidence: 99%